Modeling Modernity: Instruction Books and the History of Modern Sculpture. (2nd October 2018) - Droth, Martina
Abstract : What did modern sculpture entail in the early twentieth century? Scholarship has consistently identified sculpture's modernity with the adoption of direct carving and the rejection of clay modeling, but this article challenges such a dichotomy by examining three instruction books on sculpture published in Britain in the early twentieth century. The books are characteristic of a genre of technical writing that promotes clay modeling as the foundation of sculpture. Although significant numbers of instruction books were published in the period, they have been little-studied because of their didactic nature; yet in their emphasis on modeling techniques, they can be approached as useful sources. My argument is driven by two considerations: that the instruction books were written by successful sculptors; and that they highlight the persistence of long-standing sculptural practices that have been excluded from standard narratives. Given the preponderance of direct carving in conceptions of modern sculpture, these books offer a counter-narrative of modernity that can revise, or at least nuance, prevailing conceptions.